POSITIVISTIC LEGAL DIALECTICS - POSITIVISTIC POST (Comparative Study of Law Towards Legal Reform - Agiyanto, Ucuk (Faculty of Law, Khairun University, 2021)
According to the post-positivist figures, basically post-positivists exist to dissect the mistakes made by positivists. Positive law based on objective, empirical and rational nature and supported by systematic, procedural and formal models has become a strong mainstream in Indonesia. The main stream makes legal science feel narrow and underdeveloped. This creates legal problems in society. On the other hand, there are new ideas that carry post-positivism in the field of law with a subjective, abstract and irrational paradigm and supported by theology and God. To overcome the legal problems mentioned above, a comparative dialectic of law between positivistic and post-positivistic law is needed so that it can form a new paradigm in law with an objective-subjective, empirical-abstract, rational-irrational nature and supported by wise systematic, procedural and formal patterns..